The Interpretive Socio-Economics of Max Weber (or the Reconstruction of a Misunderstood Methodological Programme) - Norkus, Zenonas (Sociologija. Mintis ir veiksmas, 1999)
The author of this article discusses a few questions connected with interpreting the legacy of Max Weber. First, the article poses the question of when did Weber become a sociologist? Second, it considers the way that Weber defines the relationship between economics and sociology. The questions are discussed in the historical context of development of sociology in Germany. The author suggests that Weber’s relationship with the economics is a dual one. Weber develops a sociological programme while retaining institutional affiliation with economics. The author argues that Weber’s heritage can be best understood if thought of as an interdisciplinary approach in the social sciences, now known as a rational choice approach. This issue of the journal presents the second part of the article.
Keywords: Max Weber; economics; sociology; rational choice theory